Application of Marxist Philosophy in Higher Educational Institutions in Lao PDR - Phoutthaphone, Sybuamala; Dahuai, Yu; Jing, Wu (International Journal of Asian Social Science, 2017)
Marxist philosophy is a science steeped in the strong party spirit, is the ideology weapon of the proletariat in the struggle for liberation and it helps humanity set up and solves real questions, which it based on dialectical and historical materialism. The LPRP holds Marxism-Leninism, as well as Marxist philosophy as the foundation of the political notion, leadership, and direction of the performances and implementations. Thus, Marxist philosophy applied as the fundamental course of HEIs in Lao PDR, which consists of dialectical and historical materialism. However, according to this study found that the application is weak and it is not unity, due to there are many HEIs that did not follow the policies and principles of the LPRP, as well as the nationally educational development. Therefore, the Ministry of Education and Sports, and HEIs should improve and solve these issues by enhancing and promoting about the role and significance of Marxist philosophy into teaching and learning for all HEIs in Lao PDR and the society, as well as to fulfill the policies of the LPRP and the strategy of higher educational development by paying more attention to encourage, lead, direct and invest on infrastructures of the teaching and learning of Marxist philosophy in all HEIs in Lao PDR and the application that to promote and propagandize its role and significance in the society.